Research on Spatio-temporal Evolution of Land Use and Landscape Patterns along the Yangtze River in Anhui Province - YIN Jian; ZHANG Bin; QIU Yuanhong (Renmin Zhujiang)
To explore the law of landscape change in the Yangtze River in Anhui Province,based on the land use data of Anhui section of Yangtze River Basin in 1995,2005 and 2015,this paper analyzes the landscape pattern and its changes of 1995—2005 and 2005—2015,predicts the landscape pattern of land in 2025 by the MCE-CA-Markov constrained by land type suitability,and analyzes the impact of human activities on changes in landscape patterns.The results show that:From 1995 to 2015,the cultivated land was the dominant landscape type in the region.It is predicted that the cultivated land will still occupy the dominant position in 2025,and the construction land will increase.There is an obvious correlation between the decrease of cultivated land area and the increase of construction land area.From 1995 to 2015,the regional landscape showed balanced development,and the connectivity between the landscapes decreased.In 2025,the balance of the landscape will decrease,and the degree of irregularity and fragmentation of the landscape will increase.Through the analysis of landscape development intensity,it is found that the development intensity of landscape as a whole is increasing,that of cultivated land is decreasing,and that of construction land is increasing.Human activities are the main driving force of landscape change.